Mathematics anxiety amongst the malay students : a case study in UiTM Melaka / Prof. Madya Nur Azlina Abd Aziz , Ku Fauziah Ku Baharudin and Angeline Ranjethamoney Vijayarajoo - Abd Aziz, Nur Azlina; Ku Baharudin, Ku Fauziah; Vijayarajoo, Angeline Ranjethamoney (Institute of Research, Development and Commercialization (IRDC), 2005)
It has been claimed that mathematics is a subject that many students dread and as a consequence, face anxiety. Anxiety itself needs to be defined in terms of whether anxiety is positive or otherwise and if present at all. This research investigated if all / some or none of the following factors influenced or contributed toward anxiety among UiTM students in Melaka.